Peranan Sosial Media dalam Menentukan Daerah Tujuan Wisata - Nyoman Indah Kusuma Dewi; I Putu Astawa; I Wayan Siwantara; I Gusti Agung Bagus Mataram (Jurnal Bisnis dan Kewirausahaan, 2019)
Tourism marketers are currently using technology to approach their target markets. The tourism sector not only using the internet but also started using other applications such as social media. The most important thing to change since the use of information technology is the existence of direct communication between service providers or products with buyers through channels that focus on information and data. Changes in consumer behavior also occur. Consumers are paying more attention to the importance of information and services. The use of the internet and various means of information and communication (ICT) in tourism marketing can increase the competitive power of tourism sector companies. The purpose of this study is to determine the role of social media in providing consideration for tourists, especially among young people as users of social media in making the decision to travel. The study was conducted by survey and data were analyzed with descriptive statistics. The informant stopped when interviewing reaching 30 tourists. Informants were taken by purposive sampling technique. From this study, it was concluded that teenagers, now millennials, seek information on Regional Destinations through the Internet on their cellphones and through friends and relatives. Applications used to search for information on the Internet are Facebook, Video Sharing Sites (Youtube) and Photo sharing sites such as Instagram and Flicker. They will share information and photos before and after they travel. Further research suggestion would be exploration of digital marketing.